Immunoregulatory pathways in murine leishmaniasis: different regulatory control during Leishmania mexicana mexicana and Leishmania major infections. - Alexander, J (1985)
The effect of whole body sublethal gamma irradiation on the subsequent growth of Leishmania mexicana mexicana and Leishmania major was studied in CBA/Ca and BALB/c mice. Whereas BALB/c mice are highly susceptible to both parasites developing non healing progressively growing lesions at the site of cutaneous infection, CBA/Ca mice develop small healing cutaneous ulcers following subcutaneous infection with L. major but non healing lesions following subcutaneous infection with L.m. mexicana. Prior whole body sublethal irradiation of CBA/Ca mice, but not BALB/c mice, resulted in strong resistance against infection with L.m. mexicana: no lesions developed at the site of cutaneous infection. Irradiated BALB/c mice did, however, develop small lesions which healed when infected with L. major. The protective effects of irradiation coincided with the development of delayed type hypersensitivity. Both naive and sensitized nylon wool purified lymphocytes could restore susceptibility to L. major in irradiated BALB/c mice but only lymphocytes from long term infected donor mice adoptively transferred a non healing response to irradiated CBA/Ca mice infected with L.m. mexicana. Non-irradiated, L. major infected, CBA/Ca mice, but not similarly treated BALB/c mice, were found to be resistant to subsequent infection with L.m. mexicana. On the other hand, irradiated BALB/c mice infected with L. major were resistant to subsequent infectious challenge with L.m. mexicana. We suggest that the susceptibility of CBA/Ca mice to L.m. mexicana is under the control of an as yet unidentified gene which is not dependent on the generation of T suppressor cells and is bypassed by previous infection with L. major. Therefore, BALB/c mice immunized against L. major by prior sublethal irradiation are also resistant to L.m. mexicana.